M-(n+m) -(n-x)-x p+(-m+k-p) -a-(m-a+p) -(m-a)-(k+a) m+(k-a-m) m-(a+m)-(-a-m) a-(a-b)...

0 голосов
54 просмотров

M-(n+m)
-(n-x)-x
p+(-m+k-p)
-a-(m-a+p)
-(m-a)-(k+a)
m+(k-a-m)
m-(a+m)-(-a-m)
a-(a-b)
очень надо!


Математика (17 баллов) | 54 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

-(n-x)-x = -n+x-x = -n
 p+(-m+k-p) = p-m+k-p = -m+k
-a-(m-a+p) = -a-m+a-p = -m+p
-(m-a)-(k+a) = -m+a-k-a = -m-k
m+(k-a-m) = m+k-a-m = k-a
m-(a+m)-(-a-m) = m-a-m-a+m = m
a-(a-b) = a-a+b = b
- - - - 
как-то так...)